2012
DOI: 10.2174/156720212801618956
|View full text |Cite
|
Sign up to set email alerts
|

DL-3-n-Butylphthalide, an Anti-Oxidant Agent, Prevents Neurological Deficits and Cerebral Injury Following Stroke per Functional Analysis, Magnetic Resonance Imaging and Histological Assessment

Abstract: DL-3-n-Butylphthalide (NBP) is a synthetic compound based on L-3-n-Butylphthalide which was isolated from seeds of Apium graveolens. The present study aims at evaluating the outcome of NBP given prior to and after the onset of ischemic stroke in spontaneously hypertensive rats (SHR) and normotensive Wistar Kyoto rats (WKY). Stroke was induced by the middle cerebral artery occlusion (MCAO) in SHR and WKY. For pre-treatment, NBP was administered to SHR and WKY daily for two months prior to MCAO. For post-treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…The positive effects of NBP on cerebral ischemia, including improvement of microcirculation and energy metabolism, reduction of oxidative damage and neuronal apoptosis and inhibition of the inflammatory response, have been verified in experimental models and pharmacodynamic studies (1)(2)(3)(4)(5). Our previous studies demonstrated that NBP significantly inhibits caspase-3-mediated apoptosis, and decreases stroke-induced neuron loss and autophagic activity following cerebral ischemia in diabetic rats (22,23); and attenuates amyloid-β-induced activation of Table V.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The positive effects of NBP on cerebral ischemia, including improvement of microcirculation and energy metabolism, reduction of oxidative damage and neuronal apoptosis and inhibition of the inflammatory response, have been verified in experimental models and pharmacodynamic studies (1)(2)(3)(4)(5). Our previous studies demonstrated that NBP significantly inhibits caspase-3-mediated apoptosis, and decreases stroke-induced neuron loss and autophagic activity following cerebral ischemia in diabetic rats (22,23); and attenuates amyloid-β-induced activation of Table V.…”
Section: Discussionmentioning
confidence: 96%
“…The racemic compound DL-3-n-butylphthalide (NBP), which has multiple effects on various pathophysiological processes, is considered to be beneficial for the treatment of ischemic stroke, since it has been shown to protect neuronal cells against ischemia-induced brain damage and neurotoxic damage, improve cerebral blood flow, decrease brain edema and preserve the blood brain barrier (1)(2)(3)(4)(5). Cerebrolysin is a peptide-containing preparation that also exerts beneficial effects on ischemic stroke; preclinical studies have shown that Cerebrolysin substantially improves neurological outcome and promotes neurological functional recovery following ischemia by preventing cell death, the formation of free radicals, inflammation and by counteracting excitotoxicity (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies also show that NBP has a therapeutic effect on various neurodegenerative diseases, especially vascular dementia and vascular cognitive impairment without dementia (1). In animal experiments, including our own investigations, NBP may reduce cerebral edema, decrease cerebral infarct volume, improve cerebral microcirculation, protect vascular endothelial cells, scavenge free radicals, protect mitochondria, reduce inflammation, inhibit neuronal apoptosis, counteract platelet aggregation, inhibit thrombosis and decrease the expression of β-amyloid protein and tau protein in the brain (1)(2)(3). Therefore, NBP may play a neuroprotective role by acting on multiple active targets.…”
Section: Introductionmentioning
confidence: 81%
“…Certain phthalide analogs have shown neuronal protection activity in brain injury and neurodegenerative diseases323334353637. As a major component of the Chinese herb Angelica sinensis , n-butylidenephthalide (Bdph) was tested for its ability to reduce amyloid aggregates in our DS-iPSC model.…”
Section: Resultsmentioning
confidence: 99%
“…Bdph has also been reported to improve dopaminergic neuron degeneration and α-synuclein accumulation in Caenorhabditis elegans models of Parkinson's disease32, though the underlying mechanism is still unclear. Notably, n-butylphthalide (NBP), which shares the same chemical structure as Bdph, shows strong neuron protection activity in acute brain ischemia and neural degenerative diseases3334353637. Treating AD with NBP activates MAPK53 and Akt signaling34 and attenuates Aβ accumulation, Tau overexpression and cognitive impairment in AD models.…”
Section: Discussionmentioning
confidence: 99%